Transcriptomic and Metabolomic Analysis Revealed Multifaceted Effects of Phage Protein Gp70.1 on Pseudomonas aeruginosa - Zhao, Xia; Chen, Canhuang; Jiang, Xingyu; Shen, Wei; Huang, Guangtao; Le, Shuai; Lu, Shuguang; Zou, Lingyun; Ni, Qingshan; Li, Ming; Zhao, Yan; Wang, Jing; et al. (Frontiers in Microbiology, 2016)
The impact of phage infection on the host cell is severe. In order to take over the cellular machinery, some phage proteins were produced to shut off the host biosynthesis early in the phage infection. The discovery and identification of these phage-derived inhibitors have a significant prospect of application in antibacterial treatment. This work presented a phage protein, gp70.1, with nonspecific inhibitory effects on Pseudomonas aeruginosa (P. aeruginosa) and Escherichia coli (E. coli). Gp70.1 was encoded by early gene – orf 70.1 from P. aeruginosa phage PaP3. The P. aeruginosa with a plasmid encoding gp70.1 showed with delayed growth and had the appearance of a small colony. The combination of multifaceted analysis including microarray-based transcriptomic analysis, RT-qPCR, nuclear magnetic resonance (NMR) spectroscopy-based metabolomics and phenotype experiments were performed to investigate the effects of gp70.1 on P. aeruginosa. A total of 178 genes of P. aeruginosa mainly involved in extracellular function and metabolism were differentially expressed in the presence of gp70.1 at 3 examined time points. Furthermore, our results indicated that gp70.1 had an extensive impact on the extracellular phenotype of P. aeruginosa, such as motility, pyocyanin, extracellular protease, polysaccharide, and cellulase. For the metabolism of P. aeruginosa, the main effect of gp70.1 was the reduction of amino acid consumption. Finally, the RNA polymerase sigma factor RpoS was identified as a potential cellular target of gp70.1. Gp70.1 was the first bacterial inhibitor identified from Pseudomonas aeruginosa phage PaP3. It was also the first phage protein that interacted with the global regulator RpoS of bacteria. Our results indicated the potential value of gp70.1 in antibacterial applications. This study preliminarily revealed the biological function of gp70.1 and provided a reference for the study of other phage genes sharing similarities with orf70.1.